ENVIRONMENTAL SERVICE MONITORING SYSTEM IN CONTROLLING ENVIRONMENTAL POLLUTION AT THE UJUNGE TOFU FACTORY, SUMPANG BINANGAE VILLAGE, BARRU DISTRICT, BARRU REGENCY - Aidah, Hj.; Jumria; Marsuki (P3M Stia Al Gazali Barru and Meraja media, 2023)
[Full Paper] to pdf Copyright (c) 2023 Meraja journal